Recent Trends in Information and Communication Technology Proceedings of the 2nd International Conference of Reliable Information and Communication Technology (IRICT 2017) - Saeed, Faisal; Gazem, Nadhmi; Patnaik, Srikanta; Saed Balaid, Ali Saleh; Mohammed, Fathey; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents 94 papers from the 2nd International Conference of Reliable Information and Communication Technology 2017 (IRICT 2017), held in Johor, Malaysia, on April 23-24, 2017. Focusing on the latest ICT innovations for data engineering, the book presents several hot research topics, including advances in big data analysis techniques and applications; mobile networks; applications and usability; reliable communication systems; advances in computer vision, artificial intelligence and soft computing; reliable health informatics and cloud computing environments, e-learning acceptance models, recent trends in knowledge management and software engineering; security issues in the cyber world; as well as society and information technology.
Keywords: Computational intelligence; Telecommunication; Computational Intelligence; Communications Engineering, Networks